Molecular Pairing in Plasmonic Cavity - Jinshi Li; Zujin Zhao (SmartMat)
ABSTRACT Molecular optoelectronics constitutes a pivotal aspect of molecular electronics, striving to facilitate information communication and molecular computing via light–matter interactions. Plasmonics, meanwhile, holds a central position in molecular photonics and nanoelectronics, bridging the nanoscopic and mesoscopic length scales. By confining light to dimensions far beneath the diffraction limit, the interplay between plasmons and molecular junctions finds applications in switching, sensing, trapping, and energy harvesting. Prior research has established plasmonic cavities as potent optical tweezers for near‐field trapping of biomolecules such as DNA or linearly conjugated molecular junctions, accomplishing this without causing irreversible molecular damage. However, controlling through‐space π–π interactions between monomers without altering their chemical properties and conformations remains a formidable challenge.